Human interference with wildlife surveys: a case study from camera-trapping road underpasses in Costa Rica - Eleanor Flatt; Hilary Brumberg; Marco Hidalgo; Andrew Whitworth (Oryx)
Camera traps are widely used to study wildlife. However, theft and vandalism are frequent, resulting in millions of dollars in financial losses and large data gaps in research. Here we report on the impacts of camera-trap theft on a study examining wildlife movement under highway bridges in south-west Costa Rica. Even with metal cases, locks and signs installed on all camera traps, 65% were stolen. The working camera traps accumulated a total of 167 trap-nights and detected only two wild mammal species, eight bird species and one reptile species, as well as three domestic animal species and people. This limited number of wild species was unexpected given the known presence of wide-ranging megafauna and a diverse terrestrial mammal community in the region. The pervasive theft of camera traps leads to data gaps and impairs the potential for research in the region, and we discuss the potential additional reasons for detecting only a small number of species. Our findings highlight the need for solutions to camera-trap theft, to limit financial and data losses for conservation.